2017
DOI: 10.1186/s12974-017-0952-0
|View full text |Cite
|
Sign up to set email alerts
|

Priming astrocytes with TNF enhances their susceptibility to Trypanosoma cruzi infection and creates a self-sustaining inflammatory milieu

Abstract: Background: In conditions of immunosuppression, the central nervous sty 5ystem (CNS) is the main target tissue for the reactivation of infection by Trypanosoma cruzi, the causative agent of Chagas disease. In experimental T. cruzi infection, interferon gamma (IFNγ) + microglial cells surround astrocytes harboring amastigote parasites. In vitro, IFNγ fuels astrocyte infection by T. cruzi, and IFNγ-stimulated infected astrocytes are implicated as potential sources of tumor necrosis factor (TNF). Pro-inflammatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 54 publications
0
35
0
Order By: Relevance
“…Astrocyte-born TNF may contribute to T . cruzi persistence mainly in astrocytes, as parasite-positive spots in the CNS [ 47 , 54 ]. However, in the CNS TNF expression may be restricted to these parasite-positive areas, where TNF may be rapidly consumed.…”
Section: Discussionmentioning
confidence: 99%
“…Astrocyte-born TNF may contribute to T . cruzi persistence mainly in astrocytes, as parasite-positive spots in the CNS [ 47 , 54 ]. However, in the CNS TNF expression may be restricted to these parasite-positive areas, where TNF may be rapidly consumed.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, neurological involvement is observed is the vast majority of HIV-coinfected patients (Ferreira et al, 1997;Cordova et al, 2008). Astrocytes have been proposed as parasite (Weinkauf et al, 2011;Silva et al, 2015Silva et al, , 2017, and also HIV target cells, as we and others have reported (Urquiza et al, 2017;Chen et al, 2020;Li et al, 2020;Proust et al, 2020).…”
Section: Discussionmentioning
confidence: 54%
“…Since chronic infection causes intense disorganization and fibrosis, it seems that preventing or limiting such events may be the best way to restore homeostasis. The application of coadjuvant drugs, such as pentoxyfylline [70] and infliximab [71], may protect the tissue from a high production of TNF-α, which is also responsible for the activation of several enzymes, limiting the matrix disorganization. Unfortunately, several other molecules contribute to tissue damage, and further research is needed.…”
Section: Final Considerationsmentioning
confidence: 99%